PEDAGANG TIONGHOA DI PASAR TENGAH PEKANBARU (Studi kasus Jenis Komuditi Progres Bisnis) - Gehri Theressa; Indrawati " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This study aims to identify and analyze Chinese Traders in Pasar Tengah Kota Pekanbaru. This research is qualitative research which analyzed by desktriptif. The theory used in this research is work ethic theory and cultural value orientation by Kluckhohn. In this research Number of informants there are 6 people. Sampling technique is Purposive Sampling. Results from the field said that the ethos of work owned Chinese traders there are six factors that mempengrauhinya namely; Religion, social politics, environmental conditions, education, economic structure, intrinsic motivation. The work ethic greatly affects Chinese merchant business. And in running the business the Chinese also must be able to determine the type of komuditi who want to be a business. This type of commodity also determines the success of the business run by Chinese merchants. The Chinese believe strongly in luck or what is often called Feng Shui. The success of Chinese merchants trades in can from ancestral heritage passed down through generations. Keywords: Work ethos, Type of Commudity, Business Progress